Ways of Forming Expressive Vocabulary of Youth Sociolect (As Exemplified in French Language) - Kopytina, Natalia N.; Kuzmina, Oxana W.; Lomonosova, Yulia E.; Soboleva, Tatiana E.; Pristinskaya, Tatiana M. (Journal of History Culture and Art Research, 2017)
The article is devoted to the study of French youth discourse, which is characterized by a high degree of emotiveness with a pejorative connotation. The categories of emotiveness, expressivity and evaluation are considered to be interrelated that provides the ability of a lexical unit to participate in a communicative act as a means of conveying speaker's subjectivity and facilitates the implementation of pragmatic tasks. Special attention is paid to the description of the main means of development of expressive lexis that allows expressing a certain attitude to the reality by the linguistic juvenile community. It gives a detailed analysis of lexical-morphological means of juvenile lexis creation, including suffixes, apocopic units, reduplication and verlan. It is reported that lexical-semantic means of expressivity include those units that appeared as a result of a metaphorical and metonymic reinterpretation of general literary words. It is stressed that in the youth speech practically all lexis means only those concepts that are relevant to the users, it is not associated with the most essential phenomena of society's life. Finally, it is concluded that the elements of modern youth speech affect the development of the language of the whole French society.